GENDER INFLUENCE LANGUAGE ACQUISITION AND LEARNING OUTCOMES: A MIXED MEMETHOD (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study examines the impact of gender on the language learning process and overall learning outcomes, utilizing a mixed-method approach to provide a comprehensive analysis. The research combines quantitative data from IELTS annual results with qualitative insights drawn from an experimental word recognition test conducted among middle school students. The IELTS data reflects a consistent pattern over a five-year period, suggesting that female learners tend to achieve slightly higher scores in language proficiency assessments compared to their male counterparts. In parallel, the word recognition experiment revealed that female participants outperformed male students in terms of recall accuracy and task performance. These findings were based on carefully controlled conditions with equal participation from both genders, providing a balanced and comparative framework for analysis. The outcomes from both the standardized testing data and the classroom-based experiment indicate that gender may have a subtle yet noticeable influence on certain aspects of mental processing and language acquisition abilities. This research aims to contribute to the broader understanding of how gender dynamics can shape educational experiences, particularly in the field of second language learning, and highlights the relevance of incorporating gender as a variable in educational assessments and pedagogical strategies.